2023
DOI: 10.3389/fpls.2023.1157678
|View full text |Cite
|
Sign up to set email alerts
|

Application of CRISPR/Cas9-mediated gene editing for abiotic stress management in crop plants

Abstract: Abiotic stresses, including drought, salinity, cold, heat, and heavy metals, extensively reducing global agricultural production. Traditional breeding approaches and transgenic technology have been widely used to mitigate the risks of these environmental stresses. The discovery of engineered nucleases as genetic scissors to carry out precise manipulation in crop stress-responsive genes and associated molecular network has paved the way for sustainable management of abiotic stress conditions. In this context, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 215 publications
0
14
0
Order By: Relevance
“…Furthermore, there are some attributes related to the CRISPR technology that needs further refinement to ensure effective and precise genome modifications in plants. These include selection and understanding of preference and accessibility of Cas enzymes, identification of functional sgRNAs without off-target consequences in the genome, and improvements of the delivery technique of CRISPR ingredients [ 77 ]. Newer CRISPR-based techniques are often developed for bacterial and mammalian genome editing before being tested for plant usage [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are some attributes related to the CRISPR technology that needs further refinement to ensure effective and precise genome modifications in plants. These include selection and understanding of preference and accessibility of Cas enzymes, identification of functional sgRNAs without off-target consequences in the genome, and improvements of the delivery technique of CRISPR ingredients [ 77 ]. Newer CRISPR-based techniques are often developed for bacterial and mammalian genome editing before being tested for plant usage [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is further corroborated by Chen et al [ 93 ], who observed that the knockout of AITR genes in A. thaliana via CRISPR/Cas9 not only conferred enhanced drought tolerance but also did so without imposing fitness costs, indicating the technology’s potential for precise stress tolerance enhancement without adversely affecting plant growth or productivity. Kumar et al [ 100 ] extended these observations to Solanum lycopersicum (tomato), where CRISPR/Cas9-edited mutants exhibited improved drought stress responses, further validating the utility of this technology in enhancing drought tolerance across different plant species. Tiwari et al [ 101 ] expanded the scope of CRISPR/Cas9 applications by editing GRXS14/15/16/17 genes in tomato, achieving increased tolerance not only to drought but also to a spectrum of abiotic stresses, thereby highlighting the technology’s capacity for instilling multi-stress resilience in crops.…”
Section: Crispr-cas9 and Genome Editingmentioning
confidence: 94%
“…Similarly, the BRZ1 gene, which positively regulates the production of reactive oxygen species in the apoplastic region of tomatoes for heat tolerance, was edited using CRISPR/Cas9. Mutants of bzr1 exhibited impaired H 2 O 2 production in the apoplast, indicating its significance in temperature tolerance (Kumar et al, 2023). In lettuce, CRISPR/Cas9 was used to knock out the LsNCED4 gene, resulting in increased germination of lettuce seeds under heat stress (Devi et al, 2022).…”
Section: Genome-wide Identification Of Molecular Markers In Vegetable...mentioning
confidence: 99%